Planarity and multiple components promote organic photovoltaic efficiency by improving electronic transport. Issue 46 (19th September 2016) - Goldey, Matthew B.; Reid, Daniel; de Pablo, Juan; Galli, Giulia
Abstract : Establishing how the conformation of organic photovoltaic (OPV) polymers affects their electronic and transport properties is critical in order to determine design rules for new OPV materials and in particular to understand the performance enhancements recently reported for ternary blends. Abstract : Establishing how the conformation of organic photovoltaic (OPV) polymers affects their electronic and transport properties is critical in order to determine design rules for new OPV materials and in particular to understand the performance enhancements recently reported for ternary blends. We report coupled classical and ab initio molecular dynamics simulations showing that polymer linkage twisting significantly reduces optical absorption efficiency, as well as hole transport rates in donor polymers. We predict that blends with components favoring planar geometries contribute to the enhancement of the overall efficiency of ternary OPVs. Furthermore, our electronic structure calculations for the PTB7–PID2–PC71BM system show that hole transfer rates are enhanced in ternary blends with respect to their binary counterpart. Finally, our results point at thermal disorder in the blend as a key reason responsible for device voltage losses and at the need to carry out electronic structure calculations at finite temperature to reliably compare with experiments.